Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species - Wang, Ailing; Guan, Wei; Wang, Shuxia (Zootaxa, 2020)
Thirteen new species of the genus Stathmopoda are described from China: S. atrifusca sp. nov., S. cellifaria sp. nov., S. cornuta sp. nov., S. digitiprocessa sp. nov., S. dolichantha sp. nov., S. falsistimulata sp. nov., S. guangxiensis sp. nov., S. ingena sp. nov., S. liberata sp. nov., S. purpurata sp. nov., S. serrifasciaria sp. nov., S. similatridorsalis sp. nov. and S. spinicornuta sp. nov. Images of both adults and genitalia of the new species are provided, along with a map showing the distribution of these species.